2018
DOI: 10.15171/apb.2018.033
|View full text |Cite
|
Sign up to set email alerts
|

Mummy Prevents IL-1β-Induced Inflammatory Responses and Cartilage Matrix Degradation via Inhibition of NF-қB Subunits Gene Expression in Pellet Culture System

Abstract: Purpose: In Persian traditional medicine, application of Mummy material has been advised since hundred years ago for treatment of different diseases as bone fracture, cutaneous wounds and joint inflammation. Regarding to the claim of indigenous people for application of this material in the treatment of joint inflammation, the present study was designed to evaluate whether Mummy can revoke the inflammatory responses in chondrocytes stimulated with interleukin 1-β (IL-1β).Methods: Isolated chondrocytes at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…IL-1β is member of Interlukin family, it can cause various pathogenic changes in chondrocytes as it is found to play important role in progression if osteoarthritis. 21 , 22 In the present work it was found that expression of miR-152 was suppressed in IL-1β exposed normal chondrocytes. Also it was found that; upregulation of miR-152 expression caused a significant inhibition of IL-1β mediated apoptosis in chondrocytes.…”
Section: Discussionsupporting
confidence: 58%
“…IL-1β is member of Interlukin family, it can cause various pathogenic changes in chondrocytes as it is found to play important role in progression if osteoarthritis. 21 , 22 In the present work it was found that expression of miR-152 was suppressed in IL-1β exposed normal chondrocytes. Also it was found that; upregulation of miR-152 expression caused a significant inhibition of IL-1β mediated apoptosis in chondrocytes.…”
Section: Discussionsupporting
confidence: 58%
“…REL, also termed C-Rel, is a subunit of NF-κB, and it is well established that NF-κB serves a key role in OA (59). Morrovati et al (60) demonstrated that treatment of chondrocytes with IL-1β resulted in a significant increase in the expression level of C-Rel. However, there is still uncertainty as to whether C-Rel may serve as a therapeutic target for OA.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we explored the effects of IL-1β on the expression of aggrecan, collagen type II, aggrecanases, ADAMTS-4, and ADAMTS-5. Based on previous studies, the expression of MMP-13 was selected as the biomarker, which has recently been proven to be strongly upregulated in IL-1β-induced cartilage matrix degradation 18. As expected, IL-1β treatment significantly increased the MMP13 protein levels and decreased the collagen type II and aggrecan levels (Figure 1A).…”
Section: Resultsmentioning
confidence: 71%